2018
DOI: 10.1017/s0305741018000425
|View full text |Cite
|
Sign up to set email alerts
|

Enthusiastic Policy Implementation and its Aftermath: The Sudden Expansion and Contraction of China's Microfinance for Women Programme

Abstract: Many China scholars have explored shirking by local officials and “effective implementation,” but fewer have examined polices that are implemented with great enthusiasm. The Microfinance for Women Programme fits in this last category. Especially in Sichuan, targets for lending were set by the province, exceeded, raised by cities and counties, and then exceeded again. The immediate reason that lending took off in 2012 was the relaxation of collateral requirements that shifted the risk of defaults away from loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“… 5. Yanhua Deng, Kevin J. O’Brien, and Jiajian Chen, Enthusiastic policy implementation and its aftermath: The sudden expansion and contraction of China’s microfinance for women programme, The China Quarterly 234, 2018: 506–26. …”
mentioning
confidence: 99%
“… 5. Yanhua Deng, Kevin J. O’Brien, and Jiajian Chen, Enthusiastic policy implementation and its aftermath: The sudden expansion and contraction of China’s microfinance for women programme, The China Quarterly 234, 2018: 506–26. …”
mentioning
confidence: 99%
“…Under such circumstances, "selective implementation" and huge gaps between environmental policy and implementation, which were lamentable hallmarks of the Hu-Wen era, have given way to "over-implementation" or "enthusiastic policy implementation" in recent years [47]. Officials at each level face ever-increasing responsibility attribution pressures thanks to a number of supervision, inspection and investigation campaigns in recent years.…”
Section: Fieldwork and Datamentioning
confidence: 99%
“…That being said, while the vast majority of research is top-down, structurally-oriented, and largely neglects (or minimises) local agency, there is a small body of scholarship which examines the processes and dynamics involved in the acquisition and utilisation of financial services from the perspectives of local actors through in-depth fieldwork in the Chinese countryside. This research explores the local political economy of formal and informal financial intermediation (Hu, 2003;Ong, 2006;Tsai, 2004), and often finds that rural financial services -and even 'external interventions' such as microcredit -become 'embedded' within existing socioeconomic and socio-political contexts at the local level (Bislev, 2010(Bislev, , 2012Deng, O'Brien, & Chen, 2018;Hsu, 2017). In particular, it has been observed that access to financial information -especially with regard to subsidised loans -is differentiated based on existing social relations, power, and widening social stratification in rural society (Bislev, 2010(Bislev, , 2012Tsai, 2000Tsai, , 2004Unger, 2002;Y.…”
Section: Supply Demand and Impact Assessmentmentioning
confidence: 99%